Respiratory distress in small for gestational age infants based on local newborn curve prior to hospital discharge - Haksari, Ekawaty Lutfia; Hakimi, Mohammad; Ismail, Djauhar (Frontiers in Pediatrics, 2022)
Background: Respiratory distress in newborns, which may lead to risks of morbidity and death, is one of the reasons for a referral to the more advanced health facilities. Respiratory distress analysis in small for gestational age (SGA) infants remains controversial. SGA infants are a big problem for and burden the low-medium income countries. Frequentness of SGA infants varies, depending on birth weight curve used Objective: To learn about respiratory distress and its complications in SGA infants prior to hospital discharge. Methods: A retrospective cohort study was conducted on live- born infants at Sardjito Hospital. Singleton and gestational age 26 - 42 weeks were the inclusion criteria. The exclusion criteria included major congenital anomaly, chromosomal abnormalities, out-born infants admitted >24 hours, discharge against medical advice, and incomplete data. The samples were categorized into appropriate gestational age (AGA) and SGA by a local newborn curve. The samples were also classified as full-term (FT)-AGA, preterm (PT)-AGA, FT-SGA, and PT-SGA. Odds ratio (OR) was based on entire respiratory distress. Complications of respiratory distress analyzed were length of hospital stay, administration of oxygen, Continuous Positive Airway Pressure (CPAP), and ventilator. Kaplan-Meier and Cumulative Mortality Incidence (CMI) were used to analyze respiratory distress-induced mortality. Stata 13 was used to analyze the data. Results: There were 12.490 infants eligible for the study, consisting of 9396 FT-AGA infants, 2003 PT-AGA infants, 771 FT-SGA infants, and 320 PT-SGA infants. Nine hundred and thirty-two infants developed respiratory distress. Multivariate analysis revealed highest risk of respiratory distress in PT-SGA infants with OR 5,84 (4,28 - 7,99). The highest respiratory distress complications were found in PT- SGA infants, with significant difference (p<0,001) and mean hospital stay 23 days and ventilator use (p<0,001). CPAP use was the highest in PT-AGA infants, with p<0,001. There was no significant difference in oxygen administration among the groups. Respiratory distress-induced mortality analysis found the highest CMI in PT-SGA infants. Conclusion: PT-SGA had the highest risk of respiratory distress with complications of length of hospital stay, and ventilator use. Mortality analysis discovered the highest CMI in PT-SGA infants. We should therefore be alert when dealing with PT-SGA infants.